The Role of Knowledge Management Orientation in Driving the Performance of MSMEs - Barinta, Dunga (Universitas Airlangga, 2023)
The evaluation of a company's performance is a critical aspect when assessing the alignment of business activities with established plans. Regular performance measurement is vital for small-scale enterprises like Micro, Small, and Medium Enterprises (MSMEs). Internal challenges encountered by MSMEs, such as ineffective knowledge and information management, along with misunderstandings about the market, impede these businesses from enhancing their performance. In this context, possessing an orientation towards knowledge management and market awareness is crucial for propelling company performance. This study aims to investigate the impact of knowledge management orientation and market awareness on improving the performance of MSMEs, addressing existing research gaps and the challenges faced by these enterprises. Both knowledge management orientation and market awareness are considered influential factors for boosting MSME performance. Employing a quantitative approach with purposive sampling for data collection, the research successfully compiled data from 112 MSME practitioners in Malang, utilizing 100 datasets for analysis. Structural Equation Modeling (SEM) via the SmartPLS 3.0 software was employed for data analysis. The study's findings support previous research, affirming the significance of both knowledge management orientation and market orientation in driving improvements in MSME performance. Effectively managing and processing knowledge can serve as a long-term intangible asset for attaining competitiveness in the business landscape.